Film, art, new media : museum without walls? - Dalle Vacche, Angela (Houndmills, Basingstoke ; New York : Palgrave Macmillan, 2012)
Foreword; B.Peucker Acknowledgments Note on Contributors Introduction; A.Dalle Vacche PART I: EARLY CINEMA The Artist's Studio: The Affair of Art and Film; L.Nead Cezanne and the Lumiere Brothers; A.Dalle Vacche The Medium is a Muscle: Abstraction in Early Film, Dance, Painting; N.Andrew PART II: FILM THEORY Vertov and the Line: Art, Socialization, Collaboration; J.MacKay Quoting Motion: The Frame, the Shot, and Digital Video; T.Lundemo Malraux, Benjamin, Bazin: A Triangle of Hope for Cinema; D.Andrew Poetic Density, Ontic Weight: Post-Photographic Depiction in Victor Erice's Dream of Light; S.Dixon PART III: VISUAL STUDIES, ART HISTORY, FILM Of the Face, in Reticence; N.Steimatsky Remapping the Rural: The Ideological Geographies of Strapaese; L.Pucci PART IV: PAINTERS AND FILMMAKERS Artistic Encounters: Jean-Marie Straub, Daniele Huillet, and Cezanne; S.Shafto Two-Way Mirror: Francis Bacon and the Deformation of Film; S.Felleman PART V: FILM, MUSEUM, NEW MEDIA A Disturbing Presence? Scenes from the History of Film in the Museum; I.Christie Elegy, Eulogy, and the Utopia of Restoration-Alexander Sokurov's Russian Ark; J.Szaniawski Museums as Laboratories of Change: the Case for the Moving Image; F.Penz Right Here...Right Now...Art Gone Live!; G.Hogben Index
boek